2018
DOI: 10.5194/acp-2017-1188
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Production and transport mechanisms of NO in observations and models

Abstract: Abstract. A reservoir of Nitric Oxide (NO) in the lower thermosphere efficiently cools the atmosphere after periods of enhanced geomagnetic activity. Transport from this reservoir to the stratosphere within the winter polar vortex allows NO to deplete ozone levels and thereby affect the middle atmospheric heat budget. As more climate models resolve the mesosphere and lower thermosphere (MLT) region, the need for an improved representation of NO related processes increases. This work presents a detailed compari… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 25 publications
1
13
0
Order By: Relevance
“…Recent studies have shown that either constraining the model up to 90 km or assimilating mesospheric data improves the representation of the EPP IE (Pedatella, Liu, et al, ; Sassi et al, ; Siskind et al, ). In the Antarctic, Hendrickx et al () show EPP‐NO x underestimates despite MLT descent rates in WACCM that agree with observations. This result bolsters the argument that missing NO production is responsible for the model NO underestimates, although they also note that the model could have too much NO destruction or too strong horizontal diffusion.…”
Section: Introductionsupporting
confidence: 52%
“…Recent studies have shown that either constraining the model up to 90 km or assimilating mesospheric data improves the representation of the EPP IE (Pedatella, Liu, et al, ; Sassi et al, ; Siskind et al, ). In the Antarctic, Hendrickx et al () show EPP‐NO x underestimates despite MLT descent rates in WACCM that agree with observations. This result bolsters the argument that missing NO production is responsible for the model NO underestimates, although they also note that the model could have too much NO destruction or too strong horizontal diffusion.…”
Section: Introductionsupporting
confidence: 52%
“…Hendrickx et al () compared seven years (2007–2015) of SOFIE NO observations in the SH with simulations performed by the standard version of WACCM incorporating SD. SD‐WACCM includes a Kp‐driven auroral electron parameterization but lacks the specific D ‐region ion‐neutral chemistry and MEE precipitation that are in WACCM‐SIC.…”
Section: Discussionmentioning
confidence: 99%
“…However, above the mesopause MEE precipitation has a negligible effect, and similar to our findings using WACCM‐SIC, their modeled NO concentrations in the lower thermosphere are almost a factor 2 higher than observations. Hendrickx et al () suggest that the differences between their observations and model simulations could be attributed, at least in part, to uncertainties and challenges in determining reaction rates and branching ratios in several NO reactions involving excited state (N( 2 D)) and ground state (N( 4 S)) nitrogen. In the standard parameterization in WACCM (Jackman et al, ; Marsh et al, ) an ion pair produces 1.25 N atoms with branching ratios of 0.55 N( 4 S) and 0.70 N( 2 D).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations